Sharia Hybrid Contract Compliance of Islamic Microfinance Institutions in Jepara Regency - Sa’diyah, Mahmudatus; Gumilar, Asep Gugun; Susilo, Edi (EkBis: Jurnal Ekonomi dan Bisnis, 2020)
The purpose of this study was to examine the sharia compliance of the Hybrid Contract of the Syriah Microfinance Institution (LKMS) in Jepara Regency. This type of research is a Field Research, using a content analysis approach; to interpret data not as a series of physical events, but as symbolic symptoms to reveal the meaning contained in a text, and the understanding of the message presented. The research object selected was BMT in Jepara Regency which applies contract and unique hybrid products, namely BMT Mitra Muamalah (Mitramu) which has the product "Gold Pawn" and BMT Harapan Bersama (HARBER) which has a Musyarakah Mutanaqishah (MMq) product. The results showed that the Musyarakah Mutanaqishah (MMq) financing agreement at BMT Harapan Bersama (HARBER) Jepara was in accordance with the DSN-MUI fatwa NO: 73 / DSN-MUI / XI / 2008. Rahn’s contract which is run by BMT Mitra Muamalah Jepara is in accordance with the DSN-MUI Fatwa Number: 25 / DSN-MUI / III / 2002, and Fatwa DSN-MUI Number: 26 / DSN-MUI / III / 2002.. Weak internal and external supervision at Cooperative entities, the implementation of hybrid contracts in the field is prone to deviations and falling to "Riba".